Esthetic Replacement of Maxillary Lateral Incisor with Mary Lever Prosthesis: A Novel Conservative Approach - Sunki, Venkat Aditya; Reddy, Krishna Mohan; Krishna, CH Vamsi; Gupta, Nidhi (Journal of Orofacial Research, 2013)
Dentists often question the use of resin-bonded fixed partial dentures (RBFPDs) for reliable restoration of tooth-bound edentulous spaces. Initial attempts at bonding fixed partialdentures on teeth resulted in early failure due to debonding. In the 1980s and 1990s, improvements in preparation methods, metal alloys and bonding techniques made the RBFPD a more predictable option. This article provides a case report of a restoring a missing maxillary lateral incisor with modified Maryland with the advantages of being fixed to provide a stronger bond as well as being kinder to the periodontal tissues.